Adopting biorefinery and a circular bioeconomy for extracting and isolating natural products from marine algae - Zayed, Ahmed; M. El-Seadawy, Hosam; Attia, Eman Zekry; I. Rushdi, Mohammed; Abdelmohsen, Usama Ramadan (Frontiers in Natural Products, 2024)
Seaweeds or marine algae with their three main taxa are recognized as a potential pot for numerous products. This has been imperative to valorize their components at an industrial scale in the context of the sustainability goals of the United Nations (UN). Biorefinery approaches have been attempted for several decades to produce bioactive, biofuels, fine chemicals, and nutritional products from seaweeds.However, with the recent UN goals, climatic changes, and the global economic situation, it is essential to assess all the production processes involved concerning several factors. Numerous steps are performed following algae collection, including optimization of downstream processing (e.g., drying, extraction, and purification), in addition to suitable preservation to maintain products' integrity till their usage. Moreover, breakthroughs in biotechnologies and the biological sciences are also targeted to achieve the goals of the blue circular bioeconomy which focuses on renewable resources of foods, drug discovery, and energy, while preserving the ocean ecosystem. Hence, the current article provided new insights into the various processes to valorize marine algae in the frame of circular bioeconomy and sustainability concepts.